The effect of iPad apps on creative thinking among preschoolers in Jordan - Al Zu’bi, Mohammad Ahmad Abdelaziz; Omar Fauzee, Mohd Sofian; Kaur, Amrita (2017)
The present study examined the effectiveness of iPad as an educational technology tool on creative thinking based apps from apple store. Data from a total of 67 preschool children from one kindergarten in Amman city was included in this quasi-experimental investigation in which students in the experiment group used early creative thinking reinforcing through use iPad apps to complement their traditional way delivered early creative thinking education, within kindergarten classroom.The researchers used test of thinking creatively in action and movement (TCAM) at pre and post-test, the duration of the current study was 13 weeks one session weekly included pre and post-tests. The TCAM scores demonstrated that preschool children in the experiment group show greater gains on creative thinking skills of fluency, originality and imagination. Additional gender variable was examined in an effort to better understand the impact of the iPad intervention.